Genetic structure and life history are key factors in species distribution models of spiny lobsters. Issue 24 (18th November 2020) - Singh, Sohana P.; Groeneveld, Johan C.; Willows‐Munro, Sandi
Abstract: Aim: We incorporated genetic structure and life history phase in species distribution models (SDMs) constructed for a widespread spiny lobster, to reveal local adaptations specific to individual subspecies and predict future range shifts under the RCP 8.5 climate change scenario. Location: Indo‐West Pacific. Methods: MaxEnt was used to construct present‐day SDMs for the spiny lobster Panulirus homarus and individually for the three genetically distinct subspecies of which it comprises. SDMs incorporated both sea surface and benthic (seafloor) climate layers to recreate discrete influences of these habitats during the drifting larval and benthic juvenile and adult life history phases. Principle component analysis (PCA) was used to infer environmental variables to which individual subspecies were adapted. SDM projections of present‐day habitat suitability were compared with predictions for the year 2, 100, under the RCP 8.5 climate change scenario. Results: In the PCA, salinity best explained P. h. megasculptus habitat suitability, compared with current velocity in P. h. rubellus and sea surface temperature in P. h. homarus . Drifting and benthic life history phases were adapted to different combinations of sea surface and benthic environmental variables considered. Highly suitable habitats for benthic phases were spatially enveloped within more extensive sea surface habitats suitable for drifting larvae. SDMs predicted that present‐day highly suitable habitats for P. homarus will decrease by the year 2, 100. Main conclusions: Incorporating genetic structure in SDMs showed that individual spiny lobster subspecies had unique adaptations, which could not be resolved in species‐level models. The use of sea surface and benthic climate layers revealed the relative importance of environmental variables during drifting and benthic life history phases. SDMs that included genetic structure and life history were more informative in predictive models of climate change effects. Abstract : We constructed present‐day species distribution models (SDMs) for the widespread spiny lobster Panulirus homarus and individually for the three genetically distinct subspecies of which it comprises. The SDMs were used to reveal local adaptations specific to individual subspecies and to predict future range shifts under the RCP 8.5 climate change scenario. Our approach included both sea surface and benthic (sea floor) climate layers to recreate discrete influences of these habitats during the drifting larval and benthic adult life history phases. Our analyses confirmed that accounting for genetic partitioning in models of widespread marine species can reveal unique local adaptations, which were unresolved in models that excluded the genetic information.